(untitled) (Journal of the College of Basic Education, 2024)
This study aims to explore the impact of movement in the design of advertising prints for commercial advertisements, as movement is considered an important factor in attracting the recipient’s attention in design artworks. In order to achieve this goal, the research problem was identified, which is to identify the design processes that add visual movement to commercial advertisement designs. This requires a detailed study and attention from researchers. The results of this study will contribute to enhancing our understanding of the impact of visual movement in the design of advertising prints and guiding designers to use it effectively in commercial advertisements. The researcher defined her research with three limits: the objective limit, which is represented in studying visual movement and its role in the design of advertising prints for commercial advertisements, the spatial limit, which focuses on commercial advertisements for (Laha) magazine, published by Dar Al-Hayat in Lebanon, and finally the temporal limit, which is represented in magazines issued in 2024 AD. The researcher defined the terms related to the research topic, including: movement, visual movement. In the second chapter, the theoretical framework was addressed through two chapters: the first was about movement and attracting attention in design, focusing on the concept of movement in design and its role in attracting attention in advertisements. The second chapter dealt with the representation of movement in design elements and the role of structural elements in achieving movement and beauty in advertisement design. In the third chapter, the research procedures were studied by analyzing the designs of commercial advertisements in (Laha) magazine, using a descriptive approach in the analysis. A model was used to determine the axes of analysis and analyze the selected models. In the fourth chapter, the researcher mentioned the results. Conclusions and recommendations were made regarding the use of movement in advertisement design and studying its visual impact. The research concluded with a list of sources used in the study.